2022
DOI: 10.1088/1742-6596/2265/3/032028
|View full text |Cite
|
Sign up to set email alerts
|

Simulating tip effects in vertical-axis wind turbines with the actuator line method

Abstract: Simulation of the complex, unsteady aerodynamics characterizing Darrieus rotors requires computational tools with a fidelity higher than the ubiquitous Blade Element Momentum (BEM) theory. Among them, the Actuator Line Method (ALM) stands out in terms of accuracy and computational cost. This approach, however, still fails to resolve the vortex-like structures shed at the blade ends, overestimating turbine performance at the higher rotational speeds. Moving from this background, in this study a comprehensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The standard isotropic Gaussian kernel is used as projection function, using a β constant along the span and equal to 0.1c. This value ensures a correct description of the tip vortex core [12]. As observed in a previous study of the authors [11], this approach leads to two contrasting trends.…”
Section: Force Insertion Strategiesmentioning
confidence: 65%
See 2 more Smart Citations
“…The standard isotropic Gaussian kernel is used as projection function, using a β constant along the span and equal to 0.1c. This value ensures a correct description of the tip vortex core [12]. As observed in a previous study of the authors [11], this approach leads to two contrasting trends.…”
Section: Force Insertion Strategiesmentioning
confidence: 65%
“…The k- Shear Stress Transport (SST) model is used for turbulence closure. Discretization schemes, computational domain, and grid derive from the optimal setup found in a previous work on the same test case [12]. Figure 1a illustrates the adopted computational domain, whose dimensions are selected to minimize blockage effects and allow the blade wake to properly develop.…”
Section: Numerical Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach does not allow one to compare the effect of the mollification with that of the virtual camber effect. Melani, Balduzzi & Bianchini (2022) performed a comparison of both a fixed and rotating wing between ALM and wall-resolved Reynolds-averaged Navier–Stokes (RANS) simulations, and found that, although the correction was beneficial for the accuracy, the lift obtained using wall-resolved RANS simulations still differed from the ALM on the last 20 % of the blade, likely due to the virtual camber. Moreover, the corrections that require the use of a free-vortex wake model are not straightforward to apply, and increase the computational cost of the force evaluation.…”
Section: Introductionmentioning
confidence: 99%